F-aza-T-dCyd (NSC801845), a novel cytidine analog, in comparative cell culture and xenograft studies with the clinical candidates T-dCyd, F-T-dCyd and aza-T-dCyd - Morris, Joel (Mol Cancer Ther, 2021)
Herein 5-Aza-4’-thio-2’-β-fluoro-2’-deoxycytidine (F-aza-T-dCyd, NSC801845), a novel cytidine analog, is first disclosed and compared with T-dCyd, F-T-dCyd and aza-T-dCyd in cell culture and mouse xenograft studies in HCT-116 human colon carcinoma, OVCAR3 human ovarian carcinoma, NCI-H23 human NSCLC carcinoma, HL-60 human leukemia, and the PDX BL0382 bladder carcinoma. In three of five xenograft lines (HCT-116, HL-60 and BL-0382), F-aza-T-dCyd was more efficacious than aza-T-dCyd. Comparable activity was observed for these two agents against the NCI-H23 and OVCAR3 xenografts. In the HCT-116 study, F-aza-T-dCyd (10 mg/kg IP, QDx5 for 4 cycles), produced complete regression of the tumors in all mice with a response that proved durable beyond post-implant day 150 (129 days post-last dose). Similarly, complete tumor regression was observed in the HL-60 leukemia xenograft when mice were dosed with F-aza-T-dCyd (10 mg/kg IP, QDx5 for 3 cycles). In the PDX BL-0382 bladder study, both oral and IP dosing of F-aza-T-dCyd (8 mg/kg QDx5 for 3 cycles) produced regressions that showed tumor regrowth beginning 13-days post dosing. These findings indicate that further development of F-aza-T-dCyd (NSC801845) is warranted.